Thermometry of AlGaN/GaN 2D Channels at High Electric Fields Using Electrical and Optical Methods - S. Vitusevich; I.M. Nasieka; A. V. Naumov; V. V. Kalyuzhnyi; O. I. Liubchenko; I. O. Antypov; M. I. Boyko; A. E. Belyaev (Advanced Electronic Materials, 2023)
Abstract The active channels in AlGaN/GaN‐based heterostructures are studied under different applied electrical fields to identify the Joule heating factors affecting the temperature values in the channels. The temperature in active channels of two different lengths (30 and 180 µm) is characterized using optical methods, and electrical methods are used as a reference. The technique of optical thermometry is based on the data of micro‐photoluminescence and micro‐Raman experiments. The electrical method is based on the measurements of current–voltage characteristics for comparison. It is shown that photoluminescence‐ and electrical‐based temperature values demonstrate similar behavior and good correlation. The Raman‐based method, exploiting the temperature dependence of the frequency position of E2high vibrational band in GaN, shows a significant deviation compared with electrical‐ and luminescence‐based methods. This deviation is shown to be related to the residual mechanical strain in the layered structure and the formation of hot phonons. The influence of hot phonons and mechanical strain effects increases at high electrical load (>5 kV cm−1) and at high temperatures (>400 °C), respectively.